1984
DOI: 10.1093/ajcn/40.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iron, tin, and copper on zinc absorption in humans

Abstract: Zinc absorption as measured by body retention of [65Zn]zinc chloride or a turkey test meal extrinsically labeled with 65Zn was determined in human subjects by whole body counting after 7 days. Average 65Zn absorption from zinc chloride in persons with a high iron-absorbing capacity was similar to persons with a low capacity to absorb iron. Inorganic iron, 920 mumol (51 mg), or HB iron, 480 mumol (26 mg), inhibited 65Zn absorption from 92 mumol (6 mg) of zinc chloride. When 610 mumol of iron (34 mg) was added t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(60 citation statements)
references
References 14 publications
5
55
0
Order By: Relevance
“…However, when Zn increased, intracellular Cu did not change. These results confirm previous studies in which Fe was shown to decrease zinc absorption in humans in a dosedependent way when given in a water solution but not when given with a meal (Valberg et al, 1984;Sandstrom 1985) and when oral iron therapy impaired zinc absorption and thus zinc status in a doseindependent fashion, without affecting copper absorption (Troost, 2003).…”
Section: Effect Of Different Molar Ratios Over 55 Fe or 64 Cu Uptakesupporting
confidence: 91%
“…However, when Zn increased, intracellular Cu did not change. These results confirm previous studies in which Fe was shown to decrease zinc absorption in humans in a dosedependent way when given in a water solution but not when given with a meal (Valberg et al, 1984;Sandstrom 1985) and when oral iron therapy impaired zinc absorption and thus zinc status in a doseindependent fashion, without affecting copper absorption (Troost, 2003).…”
Section: Effect Of Different Molar Ratios Over 55 Fe or 64 Cu Uptakesupporting
confidence: 91%
“…Some divalent cations like copper, iron, cobalt, manganese and tin also decrease the intestinal zinc absorption in animal models [82], whereas heme iron in physiological doses does not inhibit zinc uptake in humans [83]. High doses of non-heme iron [83], or zinc and non-heme iron together as supplements [67] could notably decrease the absorption of zinc in humans.…”
Section: Influences On Zinc Bioavailability and Functions In Experimementioning
confidence: 99%
“…But [31] and by interactions with substances in the gut which enhance absorption, such as proteins and glucose polymers [27,29], or inhibit it such as phytates or other trace elements (Fe) which compete for common carriers [7].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, lactose and citric acid [23,29] facilitate Zn uptake by the enterocyte, whereas phytates decrease Zn absorption [22]. Iron (Fe) inhibits Zn uptake and metabolism and Zn has a similar effect on Fe absorption [3,11,13,17,31].…”
Section: Introductionmentioning
confidence: 99%